An acceptance-based intervention for children and adolescents with cancer experiencing acute pain – a single-subject study - Thorsell Cederberg, Jenny (J Pain Res, 2017)
BACKGROUND: Children and adolescents with cancer report pain as one of their most recurrent and troublesome symptoms throughout the cancer trajectory. Pain evokes psychological distress, which in turn has an amplifying effect on the pain experience. Acceptance-based interventions for experimentally induced acute pain predict increased pain tolerance, decreased pain intensity and decreased discomfort of pain. The aim of this study was to preliminarily evaluate an acceptance-based intervention for children and adolescents with cancer experiencing acute pain, with regard to feasibility and effect on pain intensity and discomfort of pain. METHODS: This is a single-subject study with an AB design with a nonconcurrent multiple baseline. Children and adolescents aged four to 18 years undergoing cancer treatment at the Children’s University Hospital, Uppsala, Sweden, reporting sustained acute pain were offered participation. Pain intensity and discomfort of pain were measured during baseline and at post-intervention. The intervention consisted of a pain exposure exercise lasting approximately 15 minutes. RESULTS: Five children participated in the study. All participants completed the intervention and reported that it had helped them to cope with the pain in the moment. All participants reported decreased discomfort of pain at post-measurement, three of whom also reported decreased pain intensity. CONCLUSION: The results suggest that an acceptance-based intervention may help children and adolescents with cancer to cope with the pain that is often associated with cancer treatment in spite of pharmacological pain management. The results are tentative but promising and warrant further investigation.